+0  
 
0
151
1
avatar+105 

3x+6y  x= -3, y=6

 Sep 16, 2018
 #1
avatar+2339 
+1

Substitute in the given value for x and y into the given expression and evaluate.

 

\(-3x+6y; x=-3, y=6\\ -3*-3+6*6\\ 9+36\\ 45\)

.
 Sep 16, 2018

17 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.